The Effect Of Vaasa Kushmanda Khanda In The Management Of Amlapitta-A Controlled Comparative Clinical Study - ARUN , N P; OOPA , BHAT M D (International Research Journal of Ayurveda & Yoga, 2024)
Amlapitta is a vidagdha Pitta vyadhi, being the result of a faulty diet and life style adaptations. An increased amla guna and dravatha of Pachaka pitta due to pitta prakopaka ahara vihara leads to Vidagdhajirna. Further the vidagdha anna achieves Shuktha paka and develops Avipaka, Klama, Utklesha, Gourava, Hrid kanta daha, Tiktha-amla udgara and Aruchi clinically. The symptoms of Amlapitta explained in Ayurveda are nearer clinical entity with Gastritis. An inflammation of stomach lining The objective of the study is to evaluate and compare the efficacy of Vaasa kushmanda khanda and Pippali khanda in the management of Amlapitta. 40 patients diagnosed with amlapitta were randomly assigned equally to two groups (A and B). Group A received the trial drug Vaasa kushmanda khanda and Group B received Pippali khanda for a 30 days. Statistical analysis revealed that both the interventions were effective in the management of Amlapitta with a significant overall improvement in Group A compared to group B. The Vaasa kushmanda khanda has given maximum result on the Tikta amla udgara, Klama and Hrid –Kanta Daha followed by Avipaka, Aruchi, Utklesha and Gourava. (By comparing t’ value).with the symptoms of upper abdominal pain, nausea, vomiting, bloating, loss of appetite and heartburn.